mRNA Vaccine: How to Meet the Challenge of SARS-CoV-2 - Jin, Yingqi; Hou, Chen; Li, Yonghao; Zheng, Kang; Wang, Chuan (Frontiers in Immunology, 2022)
Coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) with high infectivity, pathogenicity, and variability, is a global pandemic that severely affected public health and the world economy. The development of safe and effective vaccines is crucial to the prevention and control of an epidemic. As an emerging technology, mRNA vaccine is widely used for infectious disease prevention and control and has significant safety, efficacy, and high production. It has received support and funding from many pharmaceutical enterprises and becomes one of the main technologies for preventing COVID-19. This review introduces the current status of SARS-CoV-2 vaccines, specifically mRNA vaccines, focusing on the challenges of developing mRNA vaccines against SARS-CoV-2, and discusses the relevant strategies.